2012
DOI: 10.1177/003335491212700503
|View full text |Cite
|
Sign up to set email alerts
|

Place of Residence and Preventive Health Care for Intellectual and Developmental Disabilities Services Recipients in 20 States

Abstract: Objective. We identified trends in the receipt of preventive health care by adults with intellectual and developmental disabilities by type of residential setting.Methods. We used data from the 2008-2009 collection round of the National Core Indicators (NCI) program. Participating states drew random samples of adults receiving developmental disabilities services. The study was observational, with both self-report and report by proxy. Once the random samples were drawn in each state, data were collected using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…However, prior research results indicate that people with intellectual disabilities living in institutional settings are more likely to obtain routine dental care than are people with intellectual disabilities living with family members or independently. [20][21][22] Our sample of communitydwelling adults therefore may have encompassed the disability groups most at risk for unmet dental care needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, prior research results indicate that people with intellectual disabilities living in institutional settings are more likely to obtain routine dental care than are people with intellectual disabilities living with family members or independently. [20][21][22] Our sample of communitydwelling adults therefore may have encompassed the disability groups most at risk for unmet dental care needs.…”
Section: Discussionmentioning
confidence: 99%
“…Results of these studies have shown relatively high receipt of routine care for people living in institutional settings but significantly less frequent care among those living with family or on their own. [20][21][22] Given that underserved racial and ethnic groups and communitydwelling adults with disabilities each experience disparities in obtaining dental care, the combination of the 2 could result in especially poor receipt of routine care and high levels of unmet need. However, there has been little consideration of the potential additive effect of disability and race and ethnicity in relation to dental care.…”
mentioning
confidence: 99%
“…This phenomenon is worth continued exploration, especially as deinstitutionalization of persons with neurodevelopmental and/or psychiatric conditions continues to increase, with the number of persons living with family members having increased 68.7% in recent history (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009) ( Although least restrictive housing opportunities (e.g. living independently or with family) promote self-determination, personal control, and choice (Lakin & Stancliffe, 2007), a growing body of literature indicates a relationship between community-integrated living and poor utilization of preventative health measures (Bershadsky et al, 2012;Martínez-Leal et al, 2011). For example, individuals living in least-restrictive environments, compared to their peers living in institutions, are less likely to receive routine medical treatment, including audiology, dental, physical, and vision examinations; vaccinations; cancer screens; and other preventive medicine services (Bershadsky et al, 2012;Martínez-Leal et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings that women living at home with family caregivers were less likely to receive Pap tests corroborates recent evidence that rates of preventive screenings are generally worse for adults with intellectual disabilities who live at home rather than in residential settings. 10,25 However, an unexpected 41,42 suggesting that further research is warranted. These findings suggest that (1) women with intellectual disabilities are not receiving cervical cancer screening at recommended rates or at rates similar to women without intellectual disabilities, (2) interventions to improve Pap test rates for women in the general population have failed to reach women with intellectual disabilities, and (3) there is a need for specialized screening guidelines for women with intellectual disabilities.…”
Section: Discussionmentioning
confidence: 99%